Penguatan Ketahanan Pangan Lokal melalui Agripreneur Cengkeh Berbasis Komunitas dengan Pendekatan Manajemen Strategik di Wonosalam Jombang - Kurniawan, Aries; Cahyo Bagus Setiawan, Heri; Cahyadi, Rachmad (Universitas Muhammadiyah Gresik, 2025)
Food security and strengthening the local economy are two strategic issues in sustainable development, especially in rural areas with agribusiness potential such as Sambirejo Village, Wonosalam District, Jombang Regency. This village is known as a center for clove production that contributes significantly to farmers' income and village economic stability. This Community Service (PKM) activity is designed with a strategic management approach, which includes the process of formulating, implementing, and evaluating strategies for empowering clove farmer communities through three main stages: agripreneur training and product innovation, focus group discussions, and institutional assistance and digital marketing. The results of the activity showed that there was a strengthening of farmers' capacity in thinking strategically, forming more adaptive institutions, and expanding market access through digitalization. These findings confirm that the integration of strategic management principles in community-based agripreneurship programs can be an effective model in strengthening food security and the local economy in a sustainable manner.